FAKTOR-FAKTOR YANG MEMPENGARUHI PESEDIAAN BERAS DI KOTA BENGKULU - Sarina Sarina; Hermawati Hermawati (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2018)
The purpose of this study is to determine what factors affect the demand for rice in the city of Bengkulu. The data used in this study are secondary data obtained from BPPS report of Kota Bengkulu, public services institution, research reports and related parties, observation with institutional approach and other sources supporting this research. The data obtained were analyzed by qualitative as well as quantitatively in the form of time series data which included population data, community income and rice price from 1995 to 2014. The analysis used is multiple linear regression analysis. The results showed that demand for rice in Bengkulu city was 79% influenced by population, per capita income and rice price while 21% influenced by other factors not included in this research. Population, community income and rice prices together affect rice demand, while the partial income of the community and the price of rice does not affect the demand for rice in the city of Bengkulu